Securing the internet of things - Li, Shancang; Xu, Li D. (Syngress, an imprint of Elsevier, 2017)
"Securing the Internet of Things provides network and cybersecurity researchers and practitioners with both the theoretical and practical knowledge they need to know regarding security in the Internet of Things (IoT). This booming field, moving from strictly research to the marketplace, is advancing rapidly, yet security issues abound. This book explains the fundamental concepts of IoT security, describing practical solutions that account for resource limitations at IoT end-node, hybrid network architecture, communication protocols, and application characteristics. Highlighting the most important potential IoT security risks and threats, the book covers both the general theory and practical implications for people working in security in the Internet of Things. Helps researchers and practitioners understand the security architecture in IoT and the state-of-the-art in IoT security countermeasures ; Explores how the threats in IoT are different from traditional ad hoc or infrastructural networks ; Provides a comprehensive discussion on the security challenges and solutions in RFID, WSNs, and IoT ; Contributed material by Dr. Imed Romdhani"--Provided by publisher